Satisfaction survey on the quality of maintenance service in recreation parks in Selangor / Ahmad Izzat Nasri Ismail - Nasri Ismail, Ahmad Izzat (2014)
The recreation parks is important place to the people now day. In Selangor many places provided recreation park to the visitor in order to full fill the health life for example Taman Tasik Shah Alam, Taman Rakyat Klang and Taman Bandaran Kelana Jaya. The purpose of this study is to find out the level of satisfaction toward quality maintenance services in Recreational Parks Selangor Darul Ehsan.